2021
DOI: 10.12791/ksbec.2021.30.2.110
|View full text |Cite
|
Sign up to set email alerts
|

Seedling Quality and Photosynthetic Characteristic of Vegetables Grown Under a Spectrum Conversion Film

Abstract: This study aims to investigate the effect of spectrum conversion film on seedling quality and photosynthetic traits of leaf and fruit vegetables. Lettuce, Chinese cabbage, and cucumber seeds were sown in 50-cell plug trays filled with commercial seedling media and grown under a spectrum conversion film (SCF) and a poly-ethylene film as a control. The SCF decreased blue-green light and increased red light, and thereby increased the R/FR ratio and R/B ratio of solar spectrum, which was sufficient to affect the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 2 publications
1
5
0
Order By: Relevance
“…On the one hand, an increase in respiration intensity may indicate an increase in growth processes associated with the accumulation of biomass; on the other hand, increased respiration activity is a sign of stress in plants. Previously, in a series of works by different scientific groups, it was shown that relatively small changes in the lighting spectrum of plants caused by photoconversion covers have a significant effect on both the productivity of plants and the intensity of physiological processes in them [26][27][28][29][30]33,35,36,55,[89][90][91][92][93][94][95][96][97][98][99][100][101][102][103][104][105], which correlates with our data.…”
Section: Supplementary Materialssupporting
confidence: 91%
“…On the one hand, an increase in respiration intensity may indicate an increase in growth processes associated with the accumulation of biomass; on the other hand, increased respiration activity is a sign of stress in plants. Previously, in a series of works by different scientific groups, it was shown that relatively small changes in the lighting spectrum of plants caused by photoconversion covers have a significant effect on both the productivity of plants and the intensity of physiological processes in them [26][27][28][29][30]33,35,36,55,[89][90][91][92][93][94][95][96][97][98][99][100][101][102][103][104][105], which correlates with our data.…”
Section: Supplementary Materialssupporting
confidence: 91%
“…Before making assumptions about the reasons for the positive effect of the PCF, it should be noted that the passing of light through glass coated with luminescent nanopar-ticles was not accompanied by a noticeable increase in the intensity of the visible range. However, in the present work, as well as in a number of other works, an increase in plant productivity was demonstrated [25][26][27][28][29][30][31][33][34][35][36][37][38][39][40][41][42][43][44][45][46]. Nanosized particles can act as a protectant against UV owing to their capability to absorb and scatter ultraviolet radiation.…”
Section: Discussionmentioning
confidence: 68%
“…Several types of phosphors are used in such covers. The most widely used phosphors now are based on organic dyes [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36]. Despite all their advantages, such phosphors have a significant drawback: they lose their effectiveness very quickly due to light burnout [37].…”
Section: Introductionmentioning
confidence: 99%